Novel database for exposure to fragrance ingredients in cosmetics and personal care products - Comiskey, D.; Api, A.M.; Barratt, C.; Daly, E.J.; Ellis, G.; McNamara, C.; O’Mahony, C.; Robison, S.H.; Safford, B.; Smith, B.; Tozer, S. (Regulatory toxicology and pharmacology, 2015)
•A database of cosmetics and personal care product use data for the analysis of fragrance ingredient exposure was developed.•The data and modelling methods presented show potential as a means of calculating aggregate exposure to fragrance ingredients.•The market study of 36,446 subjects across EU and US was a valuable source of information on usage habits.•This model constitutes the most comprehensive survey of habits and practices data for personal care and cosmetics.•Statistical analyses show the robustness of the data and the ability to estimate aggregate consumer product exposure. Exposure of fragrance ingredients in cosmetics and personal care products to the population can be determined by way of a detailed and robust survey. The frequency and combinations of products used at specific times during the day will allow the estimation of aggregate exposure for an individual consumer, and to the sample population. In the present study, habits and practices of personal care and cosmetic products have been obtained from market research data for 36,446 subjects across European countries and the United States in order to determine the exposure to fragrance ingredients. Each subject logged their product uses, time of day and body application sites in an online diary for seven consecutive days. The survey data did not contain information on the amount of product used per occasion or body measurements, such as weight and skin surface area. Nevertheless, this was found from the literature where the likely amount of product used per occasion or body measurement could be probabilistically chosen from distributions of data based on subject demographics. The daily aggregate applied consumer product exposure was estimated based on each subject’s frequency of product use, and Monte Carlo simulations of their likely product amount per use and body measurements. Statistical analyses of the habits and practices and consumer product exposure are presented, which show the robustness of the data and the ability to estimate aggregate consumer product exposure. Consequently, the data and modelling methods presented show potential as a means of performing ingredient safety assessments for personal care and cosmetics products.